2012
DOI: 10.1089/jpm.2011.0482
|View full text |Cite
|
Sign up to set email alerts
|

A Required Third-Year Medical Student Palliative Care Curriculum Impacts Knowledge and Attitudes

Abstract: A modest, required palliative care curriculum can yield improvements in medical student knowledge and attitudes. However, expansion of the experiential component and palliative care skills training and assessment are needed for students to have more meaningful outcomes and to ultimately contribute to better patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 19 publications
3
70
0
2
Order By: Relevance
“…In the last decade, however, several interesting proposals have emerged in the literature to fill the gap. [7][8][9][10][11][12] Regarding attitudes among medical students, published studies have included a general overview 13 , an evaluation of the effects of palliative care educational interventions on affective responses to caring for dying patients and their families 10 and concerns about end-of-life care. 11 However, except for very dated studies 14,15 and a recent preliminary study on a small sample of medical students, 16 the specific relationship between medical students' attitudes toward the care of dying patients and those students' personality traits has generally been neglected in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, however, several interesting proposals have emerged in the literature to fill the gap. [7][8][9][10][11][12] Regarding attitudes among medical students, published studies have included a general overview 13 , an evaluation of the effects of palliative care educational interventions on affective responses to caring for dying patients and their families 10 and concerns about end-of-life care. 11 However, except for very dated studies 14,15 and a recent preliminary study on a small sample of medical students, 16 the specific relationship between medical students' attitudes toward the care of dying patients and those students' personality traits has generally been neglected in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated intensive programs like workshops, small group activities, interactions with patients and their families can highly influence the perceptions and leave a lasting impact. 13 Our study showed significant improvement in knowledge, pain management, and attitude scores toward palliative care following an educational session with certain limitations such as small sample size, selection of only 2 nd year undergraduates, single educational didactic session and only an immediate assessment of the impact of educational session.…”
Section: Discussionmentioning
confidence: 64%
“…Before the session, there was lack of positive attitude among the three groups toward palliative care. There was a positive change in the attitude of students toward palliative care after the session indicating the impact, 13 though it was a single didactic session. Repeated intensive programs like workshops, small group activities, interactions with patients and their families can highly influence the perceptions and leave a lasting impact.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations